Relation between surgeon volume and risk of complications after total hip arthroplasty: propensity score matched cohort study - Ravi, Bheeshma (BMJ Publishing Group Ltd., 2014)
Objectives To identify a cut point in annual surgeon volume associated with increased risk of complications after primary elective total hip arthroplasty and to quantify any risk identified. Design Propensity score matched cohort study. Setting Ontario, Canada Participants 37 881 people who received their first primary total hip arthroplasty during 2002-09 and were followed for at least two years after their surgery. Main outcome measure The rates of various surgical complications within 90 days (venous thromboembolism, death) and within two years (infection, dislocation, periprosthetic fracture, revision) of surgery. Results Multivariate splines were developed to visualize the relation between surgeon volume and the risk for various complications. A threshold of 35 cases a year was identified, under which there was an increased risk of dislocation and revision. 6716 patients whose total hip arthroplasty was carried out by surgeons who had done ≤35 such procedure in the previous year were successfully matched to patients whose surgeon had carried out more than 35 procedures. Patients in the former group had higher rates of dislocation (1.9% v 1.3%, P=0.006; NNH 172) and revision (1.5% v 1.0%, P=0.03; NNH 204). Conclusions In a cohort of first time recipients of total hip arthroplasty, patients whose operation was carried by surgeons who had performed 35 or fewer such procedures in the year before the index procedure were at increased risk for dislocation and early revision. Surgeons should consider performing 35 cases or more a year to minimize the risk for complications. Furthermore, the methods used to visualize the relationship between surgeon volume and the occurrence of complications can be easily applied in any jurisdiction, to help inform and optimize local healthcare delivery.